Textual supports of collective memory: the «transition to democracy» in Argentinean history high school text books at the beginning of 21st century - Rolland, Jorge (Historia y Memoria de la Educación, 2019)
analysis of textbooks around an unexplored subject such as the «transition to democracy» reveals a complex interplay between the official, scientific and social realms. We find a common sequence of events, with icons and similar themes and with a shared conceptual framework of meanings (referring to the so-called «antinomic dualism»), in the context of a broad dissemination framed by the 1993 and 2006 reforms. This speaks of an accepted and acceptable pedagogical product from a legal, economic, political, scientific and social standpoint. But we also come across deep historiographical disputes (about historical change and its foundations, alongside epistemology) and varied interactions with critical accounts (comprehensive and institutional ones) and social memories (of constitutional governments, human rights organizations and the military), in relation to narratives about rupture, continuity and a transition per se. This reveals that texts intertwine with the struggles over history and memory, with relevant implications for youth training.